Project Management in the Fast-paced Digital Environment - Anna KRULJACOVA; Mariana TESAROVA (Communications of International Proceedings, 2021)
The aim of this article is to describe and understand different project management approaches that represent the future of project management. This literature review article focuses on the benefits of these approaches and their usage while planning and organizing an international conference. More specifically, focus is put on Scrum, Artificial Intelligence, and Emotional Intelligence. Through the thorough review of literature, authors compare different emerging project approaches and conclude with the recommendations of their usage in the field of project management, with the specific focus on the organization of an international conference.
Keywords: Project Management; Digital Environment; Scrum; Artificial Intelligence; Emotional Intelligence